Improving the Quality of the Learning Process through the Implementation of Academic Supervision - Prasetiyo, Aldi; Tsaqib Muhes, A. Dzofron Abiyyu (Khalifah : Jurnal Pendidikan Nusantara, 2024)
Improving the quality of learning requires academic supervision through academic supervision shows that the existence of systematic and grounded supervision can have a positive impact on the quality of teaching. The purpose of this study is to identify the main roles of academic supervision implementation that affect the quality of the learning process, as well as the extent to which the effectiveness of academic supervision can contribute to improving the quality of learning in schools. The method used in this research is a qualitative approach with a case study method The object of this research is located at Darussalam Tulungagung Integrated Junior High School. The main sources of informants in this study are school principals who are responsible for planning and implementing academic supervision, as well as teachers and teaching staff who are the subject of the supervision. In addition, students were also involved as informants to provide their views on the influence of supervision on the quality of learning they receive. Data collection techniques in this study used interviews, observation and documentation. Data analysis techniques applied Miles and Huberman's theory of data reduction, data presentation, and conclusion. The results show that academic supervision that applies participatory approaches, such as classroom observations with immediate feedback, reflective discussions, and training tailored to teachers' needs, significantly improves teachers' ability to design and implement learning. Teachers who routinely receive quality academic supervision experience progress in implementing more diverse and innovative learning strategies.